Goal orientation as a motivation model and self-confidence among tennis players of different levels of success - Lepir Duško; Dobraš Radenko; Vučković Igor; Dragosavljević Proko (University Educons, Faculty of Sports and Tourism, Novi Sad, 2014)
The goal of this research was to determine differences between the successful and less successful tennis players regarding their goal orientation and self-confidence, as well as to examine the correlation between these two psychological constructs. Active male tennis players (N=40), ranked on the senior list of the Tennis Federation of Austria, age 18 to 26, filled in the TEOSQ-D1 questionnaire (Würth, Alfermann and Saborowski, 1999), and CSI questionnaire (Vealey, 1986), just before the national senior championship of Austria. After categorising a 'successful tennis player' as one ranked in top 100 (N=20), and a 'less successful' one as ranked outside top 100 (N=20), analyses of their differences concerning goal orientation and self-confidence were conducted by means of the T-test, but no statistically significant differences were found for any scale. Pearson's coefficient for the entire sample showed that task orientation correlate significantly with the sport confidence trait (r= 0,451; Sig.= 0,05), and to a certain extent with sport-confidence as a state (r= 0,387; Sig.= 0,092), but that correlation is not statistically significant at the level Sig.< 0,05. For the result/ego scale orientation, there were no significant correlations with sporting-confidence. Guidelines for future research are based on the development of a more adequate system for evaluation of success in sport, and also on increasing of sample size. This could be very helpful for making more reliable conclusions about the influence of goal orientation preference on sport-confidence and sport success, which could justify the utilization of this psychological construct for practical purposes.